The Relationship between the Intensity of Social Media Use and the Level of Digital Literacy in Informatics Subjects for Grade VIII Students of SMP Negeri 8 Salatiga - Saputri, Witkan; Yuliana Tien Bayangkhariwati Tacoh (Universitas Negeri Padang, 2025)
The study aims to determine the intensity of social media use and students' digital literacy level's relationship. Along with the times, social media is an essential part that is inseparable in everyday life. It is crucial to understand how the use of social media affects students in accessing and utilizing social media in learning. This research uses a quantitative method with a correlational approach. Correlational research in determining the two variables' relationship. The two variables to be tested are the intensity of social media use (X) and digital literacy (Y). Sampling using Cluster Random Sampling technique by taking 1 class totaling 32 students. The questionnaire with a Likert scale of 1-4 used to collect data. There was a significant relationship between the intensity of social media use and students' digital literacy level with a correlation value of 0.778. The results show that the higher the level of intensity of students' social media use, their digital literacy skills. This study provides suggestions for a more in-depth digital literacy development program.